Las Ramblas and Cambrils attacks (2017): analysis of public television coverage by TVE, TV3 and Betevé and proposals for improvement - Sancho-Ligorred, Belén; Rodríguez, Pepe (Estudios sobre el Mensaje Periodístico, 2022)
The terrorist attacks on Las Ramblas in Barcelona and Cambrils in August 2017 attracted a great deal of media attention. The role of the media is fundamental in crisis situations, and public broadcasters are particularly important in serving citizens and guaranteeing their right to information. This study analyses the news coverage of these attacks by three public television channels (TVE, TV3 and Betevé). It describes their involvement, their news strategies and their malpractices and, finally, puts forward a series of proposals for action and improvement aimed at improving the professional and ethical training of journalists who interact with disaster scenarios.
Keywords: Journalism; Las Ramblas and Cambrils attacks; public television; terrorism